Analysis Of The Authority Of The Tni Navy Helicopter Pilots In Maritime Law Enforcement In Indonesian Sea Territories - Paath, Ardy Agustinus; Pramono, Agung; Nuhartonosuro, Imam Munajat (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
Indonesia's vast waters make maritime law enforcement an important aspect in maintaining national sovereignty and security. Indonesian Navy (TNI AL) helicopters have a strategic role in maritime surveillance operations with the ability to detect illegal activities faster than patrol boats. However, to date, the authority of helicopter pilots in direct legal intervention is still limited, so that the effectiveness of operations is often hampered. In addition, the lack of coordination with patrol boats, limited fleet size, and minimal support for sophisticated technology are the main obstacles that reduce the efficiency of maritime law enforcement. This study aims to analyze the authority of TNI AL helicopter pilots in maritime law enforcement, identify the obstacles faced, and provide recommendations to improve the effectiveness of maritime operations. The research method used is a qualitative approach, with data collection techniques through in-depth interviews with five respondents, consisting of two TNI AL helicopter pilots, one operational officer, one maritime law expert, and one maritime defense analyst. In addition, operational observations were conducted to understand the real challenges in the field. The results of the study show that helicopter pilots only have a role as a supervisory element without the legal authority to stop or inspect ships. The main obstacles to operational effectiveness are the absence of clear regulations regarding the legal role of helicopter pilots, suboptimal coordination with patrol vessels, limited aerial monitoring technology, and the small number of helicopters in operation. To overcome these problems, regulatory revisions are needed to clarify the authority of helicopter pilots in law enforcement operations, modernization of communication and navigation systems to improve coordination with maritime elements, and the addition of the helicopter fleet to expand the scope of maritime surveillance. With these strategic steps, it is hoped that the effectiveness of maritime law enforcement operations can increase significantly, so that the security and sovereignty of Indonesian waters can be better maintained